Improving German Reading Comprehension Skill Through Applying of SQ3R Teaching Strategy - Fauzan Adhima; Ellychristina D. Hutubessy; Azizah Hanoum Siregar (Raja Zulkarnain Education Foundation, 2025)
Reading comprehension is still considered as a part of new literacy required to encounter in the Smart Society era. In addition to students ability to understand readings and can get used to utilize the internet access to read information. The SQ3R teaching Strategy is an excellent strategy for both understanding and remembering information. The purpose of this research is to improving of reading comprehension through applying SQ3R (Survey, Question, Read, Recite, Review). The type of this research is a Classroom Action Research (CAR), it contains of 2 cycles and each cycles was held in one times learning. Each cycles consists of four phases, they are planning, acting, observing, and reflecting. Research subject are lecturer and 4th semester students on german language education at the Jakarta State University. Source of data are derived from lecturer and students. Data collection techniques that used are interview, observation, test, and documentation. Data validity techniques is tested by using data content. Based on the results of this study that student learning outcomes increased from the average in cycle I 65.85 and cycle II was 87.15. Students who completed the KKM in the first cycle were 56% and the second cycle reached 96%. The conclusion of the research is the applying of SQ3R teaching stategy can improve reading comprehension skill among 4th semester students on german language education at the Jakarta state University